2018
DOI: 10.1111/ped.13505
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of response toIVIGin pediatric immune thrombocytopenic purpura

Abstract: For new-onset ITP in patients aged >2 years, corticosteroid therapy in addition to IVIG may be considered as the initial treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…A recent Japanese study showed that children ,23 months of age (n 5 24) were more likely to achieve a better PC response at the 2-week mark following therapy than older children ($23 months; n 5 29). 35 However, in that study, the initial rise in PC in the first 24 hours was not described. We found a trend for older children to show a less brisk increment in PC.…”
Section: Discussionmentioning
confidence: 77%
“…A recent Japanese study showed that children ,23 months of age (n 5 24) were more likely to achieve a better PC response at the 2-week mark following therapy than older children ($23 months; n 5 29). 35 However, in that study, the initial rise in PC in the first 24 hours was not described. We found a trend for older children to show a less brisk increment in PC.…”
Section: Discussionmentioning
confidence: 77%
“…Notably, demographic (age, sex), clinical (disease onset, preceding infection or vaccination), or biological (platelet counts at diagnosis) were already reported to be not only associated with (11), but also predictive of prolonged disease (13). Besides, previous publications used linear regression to describe platelet count evolution over time but reported conflicting results, this evolution being related (14) or not (15) with disease evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al found that patients with chronic ITP had significantly lower platelet counts one and three months after diagnosis than patients with acute ITP (14). On the contrary, Higashide et al found no association between ITP progression and platelet counts at 12 months (15).…”
Section: Introductionmentioning
confidence: 99%
“…10,37 However, these variants are rare and insufficient to explain the large proportion of non-responders. Retrospective case series have suggested that IVIg-resistant patients have higher rates of leukocyte count ≤7 × 10 9 /L, 47 age above 2 years, a platelet count <9 × 10 9 /L, 48 and a higher expression of IFNγ in peripheral blood mononuclear cells. 49 Although the absence of leukocytosis could be associated with a noninflammatory phenotype, potentially pointing to the absence of autoinflammatory or postinfectious reactive autoimmunity, this is in contrast with the increased IFNγ expression.…”
Section: Findings Of Othersmentioning
confidence: 99%